2012
DOI: 10.1590/s1806-83242012000300005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mouthrinses and simulated toothbrushing on the surface roughness of a nanofilled composite resin

Abstract: The aim of this study was to determine the influence of mouthrinses on the surface roughness of a nanofilled composite resin after toothbrushing. One hundred nanofilled composite resin specimens were prepared and randomly distributed into two groups-brushed and non-brushed-and then assigned to five subgroups, according to the mouthrinse solutions (n = 10): Colgate Plax Fresh Mint, Oral B, Cepacol, Colgate Plax, and artificial saliva. Each sample was immersed in 20 mL of the mouthrinses for 1 minute, 5 days per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 25 publications
3
46
0
15
Order By: Relevance
“…However, the use of mouthrinses may produce deleterious side-effects on the surface and physical properties of restorative materials (2). According to Ozer et al (3), the detrimental effects of mouthrinses on resin composites must be taken into account.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of mouthrinses may produce deleterious side-effects on the surface and physical properties of restorative materials (2). According to Ozer et al (3), the detrimental effects of mouthrinses on resin composites must be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Almeida et al (4) reported that the degradation of resin composites involves water sorption that results in a decrease in hardness and this mechanism is mainly dependent on the composition of the ‘polymeric matrix’. They have mentioned that the formulation of commercially available mouthrinses contains various substances, such as water, antimicrobial agents, salts, preservatives and, in some cases, alcohol (2,4,5). ‘Alcohol’ in the mouthrinses and low pH may soften the resin composite restorative materials (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, vários materiais restauradores estéticos têm sido criados para melhorar o desempenho destes, tanto no aspecto da estética quanto no funcional. No entanto, estes materiais ainda se deterioram na presença de alguns fatores da cavidade bucal (SETTEMBRINI et al, 1995) como os agentes antissépticos (TRAUTH et al, 2012) e bebidas consumidas pelos pacientes (ERTAS et al, 2006;LEE e POWERS, 2007;GODOI, 2009). …”
Section: In Nt Tr Ro Od Du Uç çã ãO Ounclassified
“…No entanto, os materiais restauradores odontológicos disponíveis no mercado, ainda sofrem alterações nas suas propriedades físicas, químicas e mecânicas frente a algumas condições da cavidade oral como por exemplo, o consumo de bebidas com pigmentos (GODOI et al, 2010) e o uso de enxaguatórios bucais (TRAUTH et al, 2012).…”
Section: Análise Dos Materiais Restauradores Odontológicos Submetidosunclassified